2014
DOI: 10.1371/journal.pone.0095562
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Human Trefoil Factor 3 Gene Promoter

Abstract: Human trefoil factor 3 (hTFF3) is a small-molecule peptide with potential medicinal value. Its main pharmacological function is to alleviate gastrointestinal mucosal injuries caused by various factors and promote the repair of damaged mucosa. However, how its transcription is regulated is not yet known. The aim of this study was to clone the hTFF3 gene promoter region, identify the core promoter and any transcription factors that bind to the promoter, and begin to clarify the regulation of its expression. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Amongst its many targets, SP1 can also work together with ERα to regulate the expression of many E2-responsive genes, as reported in a study utilising BC cells [ 44 ]. A previous study of the human TFF3 promoter in colon cancer cells had also found that the transcription of TFF3 was precisely controlled by an SP1 binding site, corroborating the results obtained in our experiments [ 45 ]. Hence, there appears to be a combinatorial control of TFF3 expression by chronic tamoxifen exposure in EC cells; the hypomethylation of the TFF3 promoter to potentially increase availability of TF binding sites as well as the specific increase in phospho-c-JUN activity and SP1 expression that interact with the binding sites on TFF3 promoter and stimulate transcription of TFF3.…”
Section: Discussionsupporting
confidence: 92%
“…Amongst its many targets, SP1 can also work together with ERα to regulate the expression of many E2-responsive genes, as reported in a study utilising BC cells [ 44 ]. A previous study of the human TFF3 promoter in colon cancer cells had also found that the transcription of TFF3 was precisely controlled by an SP1 binding site, corroborating the results obtained in our experiments [ 45 ]. Hence, there appears to be a combinatorial control of TFF3 expression by chronic tamoxifen exposure in EC cells; the hypomethylation of the TFF3 promoter to potentially increase availability of TF binding sites as well as the specific increase in phospho-c-JUN activity and SP1 expression that interact with the binding sites on TFF3 promoter and stimulate transcription of TFF3.…”
Section: Discussionsupporting
confidence: 92%
“…ChIP assay was carried out as previously described ( 20 ). ChIP assays were performed using the ChIP-IT kit (Active Motif, Carlsbad, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The intestinal trefoil factor (ITF) is a low-molecular weight polypeptide reported to protect and repair the gastrointestinal mucosa through the maintenance of intestinal epithelial cell integrity and restoration of normal intestinal permeability 2 . ITF has a unique domain in which six cysteine residues in a sequence of 38 or 39 amino acid residues form three disulfide bonds.…”
mentioning
confidence: 99%